Psychodynamic day treatment program for borderline personality disorder: factors that predict outcome and dropout. Issue 11 (19th March 2021) - Pec, Ondrej; Bob, Petr; Pec, Jan; Ludvikova, Irena
Abstract : Abstract: The objective of this study was to ascertain changes in symptoms of patients with borderline personality disorder undergoing psychodynamic day treatment with a duration of 9 months and the factors that predict clinical outcome or dropouts from the program. In an observational study, demographic characteristics (age, number of psychiatric hospitalizations, number of suicide attempts, current involvement in work or study activities), day doses of antipsychotic and antidepressant medication, psychiatric symptoms, and social functioning (Health of the Nation Outcome Scales), and symptoms of dissociation (Dissociative Experiences Scale) were assessed in patients at the beginning of treatment (N = 105). Further, psychiatric symptoms and social functioning were assessed at 3 stages: beginning of the program, end of the program, and 1-year follow-up. To study the differences between baseline values and values at the end of the treatment and follow-up values, the Wilcoxon signed-rank test was used. To discover baseline factors related to the effect of the treatment, Spearman correlation coefficients were calculated. To evaluate the differences between patients who completed the program (N = 67) and patients who dropped out (N = 38), differences in baseline factors between both groups were compared, using the Mann–Whitney test for independent samples. Improvement in symptoms (Health of the Nation Outcome Scales – version for external evaluators) at the end of the therapy (N = 67, P  < .001) and at the 1-year follow-up (N = 46, P  < .001) was found. Experience of an intimate relationship was positively related to clinical improvement at follow-up examinations ( P  < .001). Predictors of dropout included a higher number of psychiatric hospitalizations ( P  = .004), suicide attempts ( P  = .004), more severe pretreatment symptoms ( P  = .002), and symptoms of dissociation ( P  = .046). The results indicate that a psychodynamic day treatment is feasible for the treatment of less clinically disturbed patients with a history of intimate relationships. Patients with a higher number of previous psychiatric hospitalizations, more suicide attempts in the past, more severe pretreatment symptoms, and symptoms of dissociation are more likely not to complete the program.